Implementasi Metode Fuzzy Analytic Hierarchy Process (F-AHP) Untuk Penentuan Kelas Unggulan Di SMPN 2 Tanjung Lago - Moh Hafiz Trisaputra; Ari Muzakir (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Education is a continuous process that contains elements of teaching, guidance, training and leadership with the specific aim of transferring various knowledge, values, and cultures. In education at a school, there must be a superior class. The superior class is a class that provides special service programs for students by developing their talents and creativity to meet the needs of students who have the potential for intelligence and talent of students. One way to determine the superior class in a school is to create a web-based application system using the F-AHP method to make it easier for the school to determine which students enter the superior class.